Morphometric analysis of somatotropic and folliculostellate cells of human anterior pituitary during ageing - Čukuranović-Kokoris Jovana; Đorđević Miodrag; Jovanović Ivan; Kundalić Braca; Pavlović Miljana; Graovac Ivana; Ajdžanović Vladimir; Ristić Nataša; Marković-Filipović Jelena; Milošević Verica (Srpski Arhiv za Celokupno Lekarstvo, 2022)
Introduction/Objective. In this study, we have pointed out the immunohistomorphometric characteristics of somatotropic (GH) and folliculostellate (FS) cells of the male pituitary gland during ageing. Methods. On histological sections of the pituitary gland of 14 male cadavers of different ages, the GH and FS cells were immunohistochemically labeled with corresponding antibodies, monoclonal anti-GH antibody, and polyclonal anti-S100 antibody, respectively. Immunopositive GH- and FS-cells were further morphometrically analyzed using ImageJ software. Results. The obtained results of morphometric analysis showed that the surface area of GH cells increased significantly with age. In these cells, the nuclear–cytoplasmic ratio gradually decreased and became significantly higher after the age of 70 years. The volume density of GH cells has not changed during ageing, while in FS cells this parameter significantly increased in the cases older than 70 years. The nuclear–cytoplasmic ratio of GH cells is negatively correlated with the volume density of FS cells. Conclusion. Based on the obtained results, we concluded that hypertrophy of GH and FS cells occurs in men with ageing and that correlation between the morphometric parameters of these two cell types indicates their mutual interaction.